Interaction between interfacial collinear griffith cracks in composite media under thermal loading - Mishra P.K.; Das S. (My University, 2025)
This article deals with the interactions between a central crack and a pair of outer cracks situated at the interface of orthotropic elastic half planes under thermomechanical loading. The mixed boundary value problem has been reduced to a pair of singular integral equations which has been solved numerically using Jacobi polynomial method. The interaction effects have been obtained in terms of stress magnification factors depending on the crack spacing and crack length. The phenomena of crack shielding and crack amplification have been depicted through graphs for different particular cases.